Takeda Izumo, Miyoshi Shōraku, Namiki Senryū, Chūshingura (The treasury of loyal retainers). Trad. por Donald Keene. Columbia University Press, New York, 1971. (X + 183 pp.) - Fierro, Carmen (Estudios de Asia y África, 1971)
-